Brief Research Report: A Comparison of Robust Tests for Homogeneity of Variance in Factorial ANOVA. Issue 2 (3rd April 2022) - Yi, Zhiyao; Chen, Yi-Hsin; Yin, Yue; Cheng, Ke; Wang, Yan; Nguyen, Diep; Pham, Thanh; Kim, EunSook
Abstract: A simulation study was conducted to examine the efficacy of nine frequently-used HOV tests, including Levene's tests with squared residuals and with absolute residuals, Brown and Forsythe (BF) test, Bootstrap BF test, O'Brien test, Z-variance test, Box-Scheffé (BS) test, Bartlett test, and Pseudo jackknife test under comprehensive simulation conditions. The results indicate that O'Brien, Levene's with squared deviations, BS, BF, and Bootstrap BF tests had adequate Type I error control, especially for O'Brien test and Levene's test with squared deviations. Under conditions of adequately controlling for Type I error, BF and Bootstrap BF tests had consistently higher power estimates across simulation conditions. Practical recommendations of guidelines for HOV test selection in factorial ANOVA designs are presented in the paper.